Praktek Manajemen Pendidikan Sekolah Kejuruan di Daerah Jawa Tengah dan Pengaruhnya Terhadap Kesiapan Kerja Siswa - Pardjono Pardjono; H. Pradoto (Universitas Negeri Malang, 2016)
In oerder to produce qualified graduates it is essential to implement the management of human resources by applying the aspects of educational management. Those aspects cover the planning, organization, leadership, evaluation, and supervision of educational activities relevant to the management of educational resources in the schools. There is a positive correlation between the implementation of educational management and the graduates' readiness for the job market, of which the r = 0.684 at the significance level of 5%.